Monte-Carlo dose computation in radiotherapy for lung at very low density. (September 2016) - Beilla, Sara; Younes, Tony; Vieillevigne, Laure; Bardies, Manuel; Franceries, Xavier; Simon, Luc
Abstract : Introduction: In radiotherapy, some limits of clinical algorithms have been reported in low-density media. When patients are treated during Deep Inspiration Breath-Hold (DIBH), lung density can fall to 0.12 g cm -3 . Dose calculation with this density must be validated, in particular for Stereotactic (SBRT) treatment. Purpose: We propose to evaluate the performance of Eclipse AAA algorithm (Varian) for SBRT lung treatment (including DIBH) with a Monte-Carlo model based on Geant4 (GATE). GATE, AAA, and measurements are compared for several phantoms including lung heterogeneity. Materials and methods: A model of the Varian TrueBeam head was modelled using GATE. Validation was achieved by comparison with measurements in a homogeneous water tank for several static fields (3 × 3 to 20 × 20 cm 2 ) and four beam modes. Subsequently, two phantoms containing layers of water-equivalent material and cork, corresponding to lung during DIBH and free-breathing (0.12 and 0.24 g cm -3 ) were implemented. Percentage depth dose (PDD) measured by Gafchromic films were compared to AAA and GATE. Results: GATE model showed a good agreement with experimental results in homogeneous and heterogeneous phantoms. In lung heterogeneity, differences were observed between AAA and measurements. These differences are higher for small fields and lower densities. As an example, for 3 × 3 field size inside a 0.12 g cm -3 heterogeneity, relative dose was 56, 6%, 56, 2%, and 67, 5% for measurement, GATE, and AAA respectively. Conclusions: In very low densities, AAA quickly showed its limits while GATE was validated. This will allow us to perform calculations for non measurable cases, for example patients treated by SBRT during DIBH.